Tanah sebagai sakralitas: Makna teologis tanah dalam tradisi tenun ikat Rote dari perspektif kaum perempuan penenun Rote Ndao - Dethan, Mesakh A.P. (KURIOS, 2025)
This article explores the theological significance of land in the Rote ikat weaving tradition from the perspective of women weavers in Rote Ndao, East Nusa Tenggara. Through a literary approach, this research reveals how the practice of prayer is not only an economic activity but also a sacred space where women connect with the land as a source of life and spiritual identity. The findings suggest that in the cosmology of Rote women weavers, land possesses a sacred dimension that is intricately linked to the practice of ikat weaving, thereby creating a unique contextual theology within the Eastern Indonesian context. Abstrak Artikel ini mengeksplorasi makna teologis tanah dalam tradisi tenun ikat Rote dari perspektif perempuan penenun di Rote Ndao, Nusa Tenggara Timur. Melalui pendekatan literatur, penelitian ini mengungkap bagaimana praktik berdoa tidak hanya sebagai aktivitas ekonomi, tetapi juga sebagai ruang sakral di mana perempuan menjalin hubungan dengan tanah sebagai sumber kehidupan dan identitas spiritual. Temuan menunjukkan bahwa dalam kosmologi perempuan penenun Rote, tanah memiliki dimensi sakralitas yang terintegrasi dengan praktik tenun ikat, menciptakan teologi kontekstual yang unik dalam konteks Indonesia Timur.